Global Dynamics of a Prey-Predator Model with Antipredator Behavior and Two Predators - Chentong Li; Yingying Zhang; Jinhu Xu; Yicang Zhou (Discrete Dynamics in Nature and Society)
In this work, we establish a new model of one prey and two predators with antipredator behavior. The basic properties on the positivity and boundedness of solutions and the existence of equilibria are established. Through analyzing the global dynamics, we find that there exist some values of the parameters such that one of the predators can be driven into being extinct by another. Furthermore, the coexistence of the three species is investigated which shows that the antipredator behavior makes the species coexist by periodic oscillation. The results give a new insight into the influence of antipredator behavior in nature selection.